Suppression therapy as novel approach for genetic diseases and cancer - Gomes-Duarte, Andreia (2017)
Premature translation-termination codons (PTCs or nonsense codons) can arise from mutations in germ or somatic cells. The introduction of a PTC into an mRNA can trigger nonsense-mediated decay (NMD), an important mRNA surveillance mechanism that typically recognizes and degrades mRNAs containing PTCs to prevent the synthesis of C-terminally truncated proteins potentially toxic for the cell. The physiological importance of NMD is manifested by the fact that about one third of genetic disease-associated mutations generate PTCs, including beta-thalassemia. In recent years, a novel therapeutic approach entitled suppression therapy has been developed based on low molecular weight compounds to induce the translation machinery to recode a PTC into a sense codon, the so called “readthrough”. Here, by using a model of constructs containing the firefly luciferase gene as a reporter gene for beta-globin transcripts that result from PTCs, we intend to prove the principle that the suppression therapy can restore enough beta-globin protein to outweight the disease manifestations of beta-thalassemia. Our preliminary results show that both the aminoglycoside G418 and non-aminoglycoside PTC124 do not seem to be able to suppress the nonsense mutation at codon 26 or 39 of the human beta-globin mRNA in cultured HeLa cells, as reflected on the firefly luciferase activity and protein levels assessed by bioluminescence assays and Western blot, respectively. Regarding future directions, a deeper study on the use of G418 and PTC124 as efficient suppression agents for the treatment of PTC-associated diseases will be performed as it offers a major potential to treat a wide range of inherited pathologies.